Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires